Uma leitura mítico-simbólica em A sombra do patriarca , de Alina Paim - Santos, José Domingos de Jesus (2025)
This dissertation aims to make a mythical-symbolic reading of the novel The Shadow of the Patriarch (1950), by the Sergipe writer Alina Paim, from the perspective of the monomyth - initiation, departure and return - established by Joseph Campbell in The Hero with a Thousand Faces (2007). In this understanding, I will highlight, in the journey of the protagonist Raquel's search for identity, the stages that characterize her development process, interpreting the myths and symbols that permeate this inner search, especially the primitive myth of the Great Mother. The present research is based on the hypothesis that Raquel, when she meets the Great Goddess in her double face, seems to enter a cycle of suffering and subsequent overcoming. In this sense, I intend to prove its presence and importance, in addition to other classic myths in the context of the protagonist's heroic journey. To this end, I rely on the theoretical and methodological contributions of the aforementioned Campbell, Mircea Eliade, Erick Neumann, and the literary critics Eleazar Meletínski, Gilbert Durand, in addition to making use, when necessary, of Carl Jung's psychoanalytic knowledge. Certainly, this research will contribute to literary studies in the field of the imaginary and to the critical fortune of Alina Paim, which is still lacking in dissemination and deeper examinations by the academy.